2021
DOI: 10.31964/mltj.v0i0.402
|View full text |Cite
|
Sign up to set email alerts
|

Cowpea (Vigna unguiculata) Extract Reduce Malondialdehyde Levels and Prevent Aortic Endothelial Cell Decline in Ovariectomized Rats

Abstract: Estrogen has anti-oxidative and anti-inflammatory properties, but its levels decrease in postmenopausal women who can trigger oxidative stress. One of the most damaging effects of ROS is lipid peroxidation, and the end product is Malondialdehyde (MDA). Similarly, aging endothelium has increased oxidative stress and endothelial cell sensitivity to apoptosis. This study aimed to determine the effect of cowpea extract on serum MDA levels, aortic endothelial cell counts, and brain MDA levels in the ovariectomy mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(38 reference statements)
1
2
0
Order By: Relevance
“…The findings elucidated that administration of IGD could decrease MDA plasma levels significantly. This finding is consistent with previous studies showing that isoflavones can reduce MDA levels in vaginal tissue, brain, and serum [16,17]. Isoflavones have a similar structure to estradiol, bind to the estrogen receptors (ERα and ERβ), and mimicking estrogenic action [21].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The findings elucidated that administration of IGD could decrease MDA plasma levels significantly. This finding is consistent with previous studies showing that isoflavones can reduce MDA levels in vaginal tissue, brain, and serum [16,17]. Isoflavones have a similar structure to estradiol, bind to the estrogen receptors (ERα and ERβ), and mimicking estrogenic action [21].…”
Section: Discussionsupporting
confidence: 93%
“…It is suggested that OVX leads to a hypoestrogenic condition that causes oxidative stress. Other studies have revealed that Rats that underwent OVX have increased MDA levels in the brain and serum [16]. Hypoestrogenism in menopausal women reduces estrogen's antioxidant action and promotes the production of free radical molecules, often known as ROS.…”
Section: Discussionmentioning
confidence: 99%
“…The content of isoflavones in IPTS is thought to act as an antioxidant capable of neutralizing free radicals and preventing the formation of MDA due to lipid peroxidation [ 51 ]. The study of Haryati et al [ 52 ] and Setyarini et al [ 53 ] showed that the antioxidant in Vigna unguiculata was able to reduce brain and serum MDA levels after OVx treatment significantly.…”
Section: Resultsmentioning
confidence: 99%